Compact Spawl in Greece: A theoretical analysis - Konstantinos Porokalidis; Foteini Zygouri (European Regional Science Association (ERSA), 2010)
Cities probably represent the most complex and creative component of man-made environment. Nowadays their structure has been altered since the obvious limits (boundaries) of the "classic city" have been changed as result of the expansion of urban functions to the rural land. The main scope of this project is to present the complex aspects of an idiomorphic phenomenon, named "compact sprawl" of the Greek cities which is stamped by the giant growth of a "latent urbanism", such as the urban sprawl with a parallel fit of compact structures within old city boundaries. Through a theoretical approach of their partial basic spatial characteristics and taking into account the reality of the Greek urban planning system, the critic approach of "out of plan areas" is seek, in relation to the tight and coherent structures of the city centers, to create a great disharmony. In particular, this phenomenon has significant inflation at the districts of dynamic cities and coastal locations due to an enormous development of tourism. The analysis showed that while the Greek system of urban planning exhibits a "functionalist practice" with adoption of binding building clauses and regulations of land use which approximates in some point, mainly in aspiration level, the principles of a compact city and at the same time deconstruction procedure is operating which does not obey to any kind of rules, subjected to the needs of the market economy and reliant to its political and social acceptance as a procedure of urbanism. The result of the specific practice is the creation of particular and severe environmental problems and mainly the destruction of the urban form and also of country's cultural identity. Some recent policies with the implementation of land use plans and building abatements may seek for the limitation of this phenomenon, but with no essential results and mainly without succeeding in convincing for the social and political convenience of the abatement of the specific kind of building.
Keywords: 330; compact city; urban sprawl; Greek urban planning; planning framework; Legal aspects; Sustainable urban patterns